ANTHROPOLOGICAL AND AXIOLOGICAL DIMENSIONS OF SOCIAL EXPECTATIONS AND THEIR INFLUENCE ON SOCIETY’S SELF-ORGANIZATION - І. M. Hoian; V. P. Budz (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The paper aimed at analyzing the anthropological and axiological dimensions of human social expectations in the aspect of the self-organization processes of social phenomena and revealing their essence. Theoretical basis. The research is based on the synergetic paradigm, the theory of shared intentionality as well as the concept of hidden influence on the processes of socialization, synchronization of social influence on moral decisions, benefits of the cooperative learning, interpretation of social expectations as epistemological norms and standards, and the concept of social support. Originality. Social expectations are considered in a synergistic relationship to their anthropological and axiological nature. The anthropological dimension of social expectations based on human nature as a mortal and rational being is outlined. The paper highlights the axiological dimension of social expectations on the ground of the need for socialization and imitation of systems of material and spiritual values in the group. The concept of stereotype and the thanatology of social expectations is substantiated. It is proved that the stereotype of social expectations is dependent on its axiological dimension, and the thanatology of social expectations is dependent on its anthropological dimension, which is based on human mortality. It has been studied out that the stereotypical and thanatological nature of social expectations significantly influences the processes of social self-organization. Conclusions. The social expectations of a person are oriented mainly toward the anthropological dimension of values since by nature a human is a mortal being. Human social expectations are mainly related to life, health, and safety showing the priority of the thanatological nature of social expectations and their futuristic content. Social expectations are also oriented towards social values. The latter is related to the collective rational nature of a person who is prone to social imitation, which affects the stereotypical nature of social expectations. Any social expectation is an axiological one. It is an expectation of material and spiritual values. The axiological dimension of social expectations has a stereotypical nature since it is linked to the specificity of collective socialization and coexistence. The anthropological dimension of social expectations has a thanatological character and is based on human nature as a mortal and at the same time rational being forming own rationality in the group. The concept of stereotypical and thanatological social expectations is promising for further scientific exploration as its methodological basis.